1990
DOI: 10.1021/j100381a055
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from semidilute solutions of nonionic surfactants (C12E5 and C12E8) and the scaling law

Abstract: Static and dynamic light scattering have been measured on D20 solutions of nonionic surfactant C12E5 in the concentration range 3-300 g dm"3 at different temperatures. The results for the semidilute solutions at higher temperatures can be explained by the scaling theory for entangled solutions of flexible polymers which exhibit phase separations. Temperature dependences of the light scattering data suggest that the "0 temperature" exists at 27-30 °C (the lower critical consolution point is 30.5 °C), which is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 1 publication
6
52
0
Order By: Relevance
“…11-24 Brown and his coworkers 11-13 studied solution properties of C 12 E 5 , C 12 E 6 , C 12 E 7 , and C 12 E 8 micelles by SLS, DLS, and pulsed field gradient NMR measurements. Similar studies were performed for C 12 E 5 , C 12 E 6 , and C 12 E 8 micellar solutions by Kato et al 16,17 They showed that the C i E j micelles grew in size with raising temperature and increasing surfactant concentration, and that intermicellar thermodynamic and hydrodynamic interactions strongly increase with concentration. Bernheim-Groswasser et al…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…11-24 Brown and his coworkers 11-13 studied solution properties of C 12 E 5 , C 12 E 6 , C 12 E 7 , and C 12 E 8 micelles by SLS, DLS, and pulsed field gradient NMR measurements. Similar studies were performed for C 12 E 5 , C 12 E 6 , and C 12 E 8 micellar solutions by Kato et al 16,17 They showed that the C i E j micelles grew in size with raising temperature and increasing surfactant concentration, and that intermicellar thermodynamic and hydrodynamic interactions strongly increase with concentration. Bernheim-Groswasser et al…”
Section: Introductionsupporting
confidence: 70%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Brown and his coworkers [11][12][13] studied solution properties of C 12 E 5 , C 12 E 6 , C 12 E 7 , and C 12 E 8 micelles by SLS, DLS, and pulsed field gradient NMR measurements. Similar studies were performed for C 12 E 5 , C 12 E 6 , and C 12 E 8 micellar solutions by Kato et al 16,17 They showed that the C i E j micelles grew in size with raising temperature and increasing surfactant concentration, and that intermicellar thermodynamic and hydrodynamic interactions strongly increase with concentration. Bernheim-Groswasser et al 24 realized by cryo-TEM observations that in the growth of the C 12 E 5 micelles thread-like or polymer-like micelles were evolved in the solutions examined, especially to the greater length in the vicinity of the lower consolute point.…”
mentioning
confidence: 99%
“…8 Dynamic Light Scattering DLS measurements were carried out to determine the translational diffusion coefficient D for the micelles by the use of the same apparatus and light source as used in the SLS studies described above. All the test solutions studied are the same as those used in the SLS studies.…”
Section: Static Light Scatteringmentioning
confidence: 99%
“…20 Oxyethylene glycol-monoethers (C i E j ) 21,22 are archetypical surfactants widely used in fundamental phase studies of microemulsions, [23][24][25][26][27] block-co-polymers, 28 and micelles. 29,30 The phase behavior of pentaethylene glycol monododecyl ether (ndodecyl pentaoxyethylene glycol ether) (C 12 E 5 ) 31,32 is particularly well-known: Pure C 12 E 5 forms cylindrical micelles but the oil-swollen C 12 E 5 micelles are wormlike with a rather high flexibility and cannot be described as rigid rods. 33,30 Several C i E j s can be used to solubilize selected PPPs 34,35 and PFs.…”
Section: Introductionmentioning
confidence: 99%